Job satisfaction and emotional competence of nurses at inpatient hospital services - Rocha,Inês (2021)
Abstract Introduction: Nurses’ job satisfaction and emotional competence are important for the safety and quality of the care provided so it is essential to measure them. Objectives: To characterize nurses’ job satisfaction and emotional competence and to evaluate the association between both variables and the nurses’ sociodemographic and professional characteristics. Methods: Descriptive-correlational, exploratory, cross-sectional quantitative study. Application of a questionnaire to 44 nurses in a hospital in the north of Portugal which includes sociodemographic and professional characterization, “Escala da Satisfação Profissional” (Job Satisfaction Scale); e “Escala Veiga de Competência Emocional” (Emotional Competence Veiga Scale). The questionnaire was validated for this study. Results: The results show that nurses are moderately satisfied professionally and perceive themselves with moderate emotional competence. Nurses’ age is positively correlated with self-motivation. Conclusion: It is essential that health organizations systematically assess nurses’ job satisfaction and emotional competence in order to implement interventions that enhance these two variables, such as nursing clinical supervision programs.